2021
DOI: 10.3727/096504021x16328213967104
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA LAMTOR5-AS1 Interference Affects MicroRNA-506-3p/E2F6-Mediated Behavior of Non-Small Cell Lung Cancer Cells

Abstract: Long noncoding RNA LAMTOR5 antisense RNA 1 (LAMTOR5-AS1) has been certified as a risk predictor and diagnostic biomarker of prostate cancer. However, the expression and exact roles of LAMTOR5-AS1 in non-small cell lung cancer (NSCLC) remain unclear. Thus, we measured LAMTOR5-AS1 expression in NSCLC and gauged its clinical value. The detailed roles and downstream working mechanism of LAMTOR5-AS1 in NSCLC were comprehensively unraveled. qRT-PCR was applied to measure gene expression. Functionally, utilizing smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Former research regarded miR-506 as a tumor suppressive role in various tumors [20][21][22]. However, its role in RCC has not yet been investigated, at least to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Former research regarded miR-506 as a tumor suppressive role in various tumors [20][21][22]. However, its role in RCC has not yet been investigated, at least to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that lncRNAs expression levels contribute to onset and progression of CRC. [50][51][52] Chen et al 53 revealed that LAMTOR5-AS1 is remarkably upregulated in non-small cell lung cancer cell tissues. Moreover, in the study conducted by Zaniani et al, 46 LAMTOR5-AS1 was overexpressed in CRC tissues.…”
Section: Discussionmentioning
confidence: 99%
“…13 Previous literature has demonstrated that LAMTOR5-AS1 may interfere with the development of different diseases, such as colorectal cancer, non-small-cell carcinoma, and prostate cancer. [14][15][16] The role of LAMTOR5-AS1 in cervical cancer has not been confirmed at this stage. Given the application of LAMTOR5-AS1 in disease, we speculated that it may play a regulatory role in cervical cancer.…”
Section: Introductionmentioning
confidence: 91%
“…LAMTOR5‐AS1 is located next to the LAMTOR5 gene and is encoded by three exons on human chromosome 1 (p13.3) 13 . Previous literature has demonstrated that LAMTOR5‐AS1 may interfere with the development of different diseases, such as colorectal cancer, non‐small‐cell carcinoma, and prostate cancer 14–16 …”
Section: Introductionmentioning
confidence: 99%